2023
DOI: 10.1200/jco.2023.41.16_suppl.e20647
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary efficacy, safety, and immunomodulatory effects of PT-112 from a phase 2 proof of concept study in patients (pts) with thymic epithelial tumors (TETs).

Abstract: e20647 Background: Immune checkpoint inhibitors (ICIs) are associated with a high risk of immune-related adverse events (irAEs) in pts with TETs (thymoma and thymic carcinoma). PT-112, a novel inducer of immunogenic cell death, has demonstrated safety and efficacy in phase I trials. We present results of an unplanned interim analysis of a phase 2, NIH IRB-approved clinical trial to evaluate the clinical activity, tolerability, and correlative immunology of PT-112 in TETs (NCT05104736). Methods: Eligible pts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PT-112 is under evaluation in several clinical trials and has previously demonstrated clinical activity in thoracic cancers, including thymoma [96]. In an ongoing phase II clinical trial for recurrent TETs (NCT05104736), ten patients have been treated to date, and eight (89%) out of nine evaluable patients achieved deceased stabilization [97]. The median PFS for thymoma has not been reached, and the median PFS for thymic carcinoma is 6.2 months.…”
Section: Targeting Ribosomal Biogenesismentioning
confidence: 99%
“…PT-112 is under evaluation in several clinical trials and has previously demonstrated clinical activity in thoracic cancers, including thymoma [96]. In an ongoing phase II clinical trial for recurrent TETs (NCT05104736), ten patients have been treated to date, and eight (89%) out of nine evaluable patients achieved deceased stabilization [97]. The median PFS for thymoma has not been reached, and the median PFS for thymic carcinoma is 6.2 months.…”
Section: Targeting Ribosomal Biogenesismentioning
confidence: 99%